Sexual Quality of Life, Sexual Knowledge, and Attitudes of Older Adults on the Example of Inhabitants Over 60s of Bialystok, Poland - Cybulski, Mateusz; Cybulski, Lukasz; Krajewska-Kulak, Elzbieta; Orzechowska, Magda; Cwalina, Urszula; Jasinski, Marek (Frontiers in Psychology, 2018)
Introduction: Aging has a strong influence on the quality of relationships and sexual functioning, but in itself does not cause a lack of sexual desire. Objectives: The aim of this study was to assess the quality of sexual life and define sexual knowledge and attitudes of older people on the example of residents of Bialystok, Poland at the age of 60 and over. Methods: The study included 170 people, inhabitants of Bialystok, Poland aged over 60: 85 students of the University of Healthy Senior and the University of Psychogeriatric Prophylaxis and 85 students of the University of the Third Age. The study used three standardised psychometric scales: Sexual Quality of Life Questionnaire-Male (SQoL-M), Sexual Quality of Life Questionnaire-Female (SQoL-F) and Aging Sexual Knowledge and Attitudes Scale (ASKAS). Results: The overall mean score for the ASKAS scale for knowledge was 65.21±12.32 and for attitudes - 124.65±22.00. The overall mean SQOL score was 62.92±18.18. Taking into account the gender of the respondents, the knowledge of men on sexuality of seniors was at the level of 63.48±12.63, while in the female group - 65.74±12.23. The attitudes of men on sexuality of seniors was at the level of 128.80±21.56, while in the female group – 123.38±22.05. Satisfaction with sex life among men (72.36±27.49) was significantly higher than among women (60.02±12.88). Discussion: The seniors were characterized by moderate knowledge and attitudes to sexuality of older people and the average level of sexual satisfaction. There was no significant relationship between knowledge on sexuality and sexual satisfaction in the study groups, and there was a positive correlation between attitudes towards sexuality and the satisfaction of sex life outside the group of men. In order to improve the knowledge of senior citizens about sexuality of old age and to overcome the taboos that are prevalent in this topic, a structured training should be provided in this field. It is desirable to conduct in-depth studies in the assessment of knowledge, attitudes and quality of sexual life in a larger research group, in order to get results for the population of the whole country.